Note on the presence of Nierembergia angustifolia (Solanaceae) in Jalisco, Mexico - García Rubio, Luz Adriana; Vargas, Ofelia; Harker, Mollie (Instituto de Ecología, A.C., 2004)
We report, for the first time, the presence of Nierembergia angustifolia in the state of Jalisco, Mexico. The distinctive characteristics of this species and an update of its known geographical distribution are discussed.